The Knowledge Levels of Pediatricians about the Vaccination against Pertussis - Ahmet Doğan; Hüseyin Dağ; Habip Gedik; Kemal Pişmişoğlu (Journal of Preventive Medicine And Care, 2018)
Objective: This study aimed to assess the knowledge and attitude levels of pediatricians in terms of the pertussis vaccine. Materials and Methods: A survey study was carried out to evaluate the knowledge and attitude levels of pediatricians working in Istanbul in terms of the pertussis vaccine between May 1, 2015 and July 1, 2015. Results: A total of 104 pediatricians who comprised of 53 male and 51 female physicians, participated in this study. It was found that 35.6% of them at low-level, 51% at middle-level and 13.5% at a high-level of knowledge. The knowledge-level scores of the pediatricians who had children were significantly higher than those of pediatricians who had not a child on pertussis vaccine. Moreover, the knowledge-level scores of the specialist doctors in terms of the pertussis vaccine were significantly higher than those of the assistant doctors. It was significant that pediatricians who had children suffering from chronic diseases had greater knowledge-level scores in terms of the pertussis vaccine than those who had children without any disease. Conclusion: The knowledge and awareness of physicians in terms of the pertussis vaccine should be increased with in-service trainings, as the surveyors presented an insufficient knowledge level.
Keywords: Pertussis vaccine